Acute Kidney Injury in the 2019 Novel Coronavirus Disease - Jing-Yi Qian; Bin Wang; Bi-Cheng Liu (Karger Publishers, 2020)
Background: The 2019 novel coronavirus disease (COVID-19) is a newly defined serious infectious disease caused by the SARS-CoV-2 virus. The epidemic started in Wuhan, China, in December of 2019 and quickly spread to over 200 countries. It has affected 4,258,666 people, with 294,190 deaths worldwide by May 15, 2020. COVID-19 is characterized by acute respiratory disease, with 80% of patients presenting mild like flu-like symptoms; however, 20% of patients may have a severe or critical clinical presentation, which likely causes multiple organ injuries (e.g., kidney, heart, blood, and nervous system). Among them, acute kidney injury (AKI) is a critical complication due to its high incidence and mortality rate. Here we present a review of the current understanding of AKI in COVID-19. Summary: COVID-19 is a catastrophic contagious disease caused by the coronavirus, and the AKI induced by COVID-19 significantly increases the mortality rate. In this review, we summarize the clinical characteristics of COVID-19 induced AKI by focusing on its epidemiology, pathogenesis, clinical diagnosis, and treatment. Key Messages: Multiple studies have shown that COVID-19 may involve the kidneys and cause AKI. This article reviews the characteristics of COVID-19-induced AKI largely based on up-to-date studies in the hope that it will be helpful in the current global fight against and treatment of COVID-19.